Optical emission spectra of a copper plasma produced by a metal vapour vacuum arc plasma source - Yotsombat B. (2014)
Optical emission spectroscopy in the range 200-800 nm was applied for investigation of the copper plasma produced by a metal vapour vacuum arc plasma source. The experiments were conducted for the cases when the plasma was guided by straight and Ω-shaped curved solenoids as well as without solenoids, and also for different vacuum conditions. It was found that, besides singly- and doubly-charged ions, a relatively high concentration of excited neutral copper atoms was present in the plasma. The relative fraction of excited atoms was much higher in the region close to the cathode surface than in the plasma column inside the solenoid. The concentration of excited neutral, singly- and doubly-ionized atoms increased proportionally when the arc current was increased to 400 A. Some weak lines were attributed to more highly ionized copper species and impurities in the cathode material.